-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathSum_of_powers_of_two.thy
63 lines (56 loc) · 1.64 KB
/
Sum_of_powers_of_two.thy
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
(* Sum_of_powers_of_two.lean
-- Proofs of \<Sum>k<n. 2^k = 2^n-1
-- José A. Alonso Jiménez <https://jaalonso.github.io>
-- Sevilla, September 24, 2024
-- ------------------------------------------------------------------ *)
(* ---------------------------------------------------------------------
-- Prove that
-- 1 + 2 + 2² + 2³ + ... + 2\<^sup>n⁾= 2\<^sup>n\<^sup>+\<^sup>1 - 1
-- ------------------------------------------------------------------ *)
theory Sum_of_powers_of_two
imports Main
begin
(* Proof 1 *)
lemma "(\<Sum>k\<le>n. (2::nat)^k) = 2^(n+1) - 1"
proof (induct n)
show "(\<Sum>k\<le>0. (2::nat)^k) = 2^(0+1) - 1"
by simp
next
fix n
assume HI : "(\<Sum>k\<le>n. (2::nat)^k) = 2^(n+1) - 1"
have "(\<Sum>k\<le>Suc n. (2::nat)^k) =
(\<Sum>k\<le>n. (2::nat)^k) + 2^Suc n"
by simp
also have "\<dots> = (2^(n+1) - 1) + 2^Suc n"
using HI by simp
also have "\<dots> = 2^(Suc n + 1) - 1"
by simp
finally show "(\<Sum>k\<le>Suc n. (2::nat)^k) = 2^(Suc n + 1) - 1" .
qed
(* Proof 2 *)
lemma "(\<Sum>k\<le>n. (2::nat)^k) = 2^(n+1) - 1"
proof (induct n)
show "(\<Sum>k\<le>0. (2::nat)^k) = 2^(0+1) - 1"
by simp
next
fix n
assume HI : "(\<Sum>k\<le>n. (2::nat)^k) = 2^(n+1) - 1"
have "(\<Sum>k\<le>Suc n. (2::nat)^k) =
(2^(n+1) - 1) + 2^Suc n"
using HI by simp
then show "(\<Sum>k\<le>Suc n. (2::nat)^k) = 2^(Suc n + 1) - 1"
by simp
qed
(* Proof 3 *)
lemma "(\<Sum>k\<le>n. (2::nat)^k) = 2^(n+1) - 1"
proof (induct n)
case 0
then show ?case by simp
next
case (Suc n)
then show ?case by simp
qed
(* Proof 4 *)
lemma "(\<Sum>k\<le>n. (2::nat)^k) = 2^(n+1) - 1"
by (induct n) simp_all
end